Self-Determination as a Mediator Between Mindfulness and Perfectionism in Theory and Practice - João Paulo Teixeira Antunes; Saúl Neves de Jesus; Marta Brás; Cláudia Carmo (SAGE Open)
Mindfulness-based interventions (MBIs) have been surging as an alternative to cognitive-behavioural therapy for perfectionism. Despite promising results, there are practical and theoretical concerns regarding high resistance from perfectionists towards developing mindfulness related capabilities. Self-Determination Motivation could provide a pathway to circumvent this problem by mediating the relationship between mindfulness and multidimensional perfectionism. Ninety-three university students filled a questionnaire containing mindfulness, perfectionism and motivation measures. Thirteen participants were then included in an 8-week MBI. Intrinsic motivation mediated the effect between mindfulness and perfectionist concerns (indirect effect = −0.09). Perfectionist concerns and strivings were both reduced post-intervention ( p  = .002). There was also a significant intragroup increase in mindfulness ( p  ≤ .001), although there were no motivational changes. Current change mechanisms underlying MBI effectiveness do not support this approach as presenting unique advantages over other cognitive-behavioural approaches. Implementing explicit motivational change into MBI interventions could provide a pathway to differentiating MBIs from other alternatives.